Properties of Z1 and Z2 Deep-Level Defects in n-Type Epitaxial and High-Purity Semi-Insulating 4H-SiC - Paweł Kamiński; Roman Kozłowski; Jarosław Żelazko; Kinga Kościewicz; Tymoteusz Ciuk (Crystals, 2024)
For the first time, the Z1 and Z2 defects with closely spaced energy levels having negative-U properties are revealed in high-purity semi-insulating (HPSI) 4H-SiC using Laplace-transform photoinduced transient spectroscopy (LPITS). In this material, after switching off the optical trap-filling pulse, either the one-electron or the two-electron thermally stimulated emission from these defects is observed at temperatures 300–400 K. It is found that the former corresponds to the Z10/+ and Z20/+ transitions with the activation energies of 514 and 432 meV, respectively, and the latter is associated with the Z1−/+ and Z2−/+ transitions with the activation energies of 592 meV and 650 meV, respectively. The Z1 and Z2 defect concentrations are found to increase from 2.1 × 1013 to 2.2 × 1014 cm−3 and from 1.2 × 1013 to 2.7 × 1014 cm−3, respectively, after the heat treatment of HPSI 4H-SiC samples at 1400 °C for 3 h in Ar ambience. Using the electrical trap-filling pulse, only the thermal two-electron emission from each defect was observed in the epitaxial 4H-SiC through Laplace-transform deep level transient spectroscopy (LDLTS). The activation energies for this process from the Z1 and Z2 defects are 587 and 645 meV, respectively, and the defect concentrations are found to be 6.03 × 1011 and 2.64 × 1012 cm−3, respectively. It is postulated that the Z1 and Z2 defects are the nearest-neighbor divacancies involving the carbon and silicon vacancies located at mixed, hexagonal (h), and quasi-cubic (k) lattice sites.